Genetic Characteristics of Restored Elk Populations in Kentucky. Issue 3 (5th January 2020) - Youngmann, Jordan L.; Deyoung, Randy W.; Demarais, Stephen; Strickland, Bronson K.; Jenkins, Gabe
Abstract : We assessed genetic diversity in restored herds of elk in Kentucky, USA, and compared genetic similarity to western source stocks. Genetic variation in the restored populations was comparable to source stocks and genetic differentiation and Bayesian clustering revealed that stocks from Utah and North Dakota, USA, contributed most to the restored populations. ABSTRACT: Translocations are a common management practice to restore or augment populations. Understanding the genetic consequences of translocation efforts is important for the long‐term health of restored populations. The restoration of elk ( Cervus canadensis ) to Kentucky, USA, included source stocks from 6 western states, which were released at 8 sites in southeastern Kentucky during 1997–2002. We assessed genetic diversity in restored herds and compared genetic similarity to source stocks based on 15 microsatellite DNA loci. Genetic variation in the restored populations was comparable to source stocks ( x ¯ allelic richness = 3.52 and 3.50; x ¯ expected heterozygosity = 0.665 and 0.661 for restored and source, respectively). Genetic differentiation among all source and restored populations ranged from 0.000 to 0.065 for pairwise FST and 0.034 to 0.161 for pairwise Nei's DA . Pairwise genetic differentiation and Bayesian clustering revealed that stocks from Utah and North Dakota, USA, contributed most to restored populations. Other western stocks appeared less successful and were not detected with our data, though our sampling was not exhaustive. We also inferred natural movements of elk among release sites by the presence of multiple genetic stocks. The success of the elk restoration effort in Kentucky may be due, in part, to the large number of elk ( n  = 1, 548), repeated releases, and use of diverse source stocks. Future restoration efforts for elk in the eastern United States should consider the use of multiple stock sources and a large number of individuals. In addition, preservation of genetic samples of founder stock will enable detailed monitoring in the future. © 2020 The Authors. The Journal of Wildlife Management published by Wiley Periodicals, Inc. on behalf of The Wildlife Society.